Evaluation of the In Vitro and In Vivo Antifungal Activity of APX001A/APX001 Against Candida auris. (4th October 2017) - Larkin, Emily; Long, Lisa; Hager, Christopher; Shaw, Karen Joy; Ghannoum, Mahmoud
Abstract: Background: Candida auris, an emerging multidrug-resistant yeast, causes deadly invasive infections with high mortality. C. auris strains often show high MICs to fluconazole and amphotericin B, and some are resistant to all 3 major antifungal classes, limiting treatment options. We tested 16 C. auris strains from a wide geographical area (Germany, Japan, S. Korea, and India) against 10 antifungals including APX001A (APXA), an antifungal with a novel mechanism of action (inhibition of the Gwt1 fungal enzyme). The prodrug APX001 (APX) is in clinical development and its efficacy was evaluated in an immunocompromised murine model of disseminated C. auris. Methods: MICs were determined by CLSI M27-A3 method. Mice were immunocompromised for the study. Treatment was initiated 2 hours post challenge. IP treatment groups included a vehicle control, APX 78mg/kg (mpk) BID, 78mpk TID, and 104mpk BID, and anidulafungin (AFG) 10mpk BID. Survival was monitored for 16d post inoculation. Results: Susceptibility . APXA had significantly lower MIC50 and MIC90 values (concentration that inhibits 50 and 90% of the tested isolates, respectively) than the other tested antifungals with a MIC90 of 0.031 µg/mL (Table 1). Survival. 100% mortality in the vehicle-treated control group occurred by 6d. Significant efficacy was observed in all APX treatment groups with 90, 100, and 80% survival observed respectively for APX 78 mpk BID; 78 mpk TID and 104 mpk BID. AFG treatment resulted in 50% survival at 16d. Mice in all of the APX treated groups had a significantly higher % survival compared with the AFG and vehicle groups. Conclusion: APXA was the most active antifungal agent in vitro . The prodrug APX resulted in significantly better survival than AFG in a C. auris disseminated infection model. Thus APX may be a viable treatment for C. auris infections. Table 1: Susceptibility of 16 C. auris isolates against antifungals Disclosures: K. J. Shaw, Amplyx Pharmaceuticals Inc.: Employee, Salary; M. Ghannoum, Amplyx Pharmaceuticals: Consultant, Research Contractor and Scientific Advisor, Consulting fee and Research grant; Cidara Therapeutics: Consultant and Research Contractor, Consulting fee and Research grant